Developing a new field of trade union activity : at regional level on behalf of Europe's regions. (Regional development studies, 1996)
This study aims to provide information on the role of the trade unions in the regions of the European Union, specifically on only that part of their work which directly relates to the regions and which determines their presence, activities and influence there. This appears to be a simple goal at first glance, but closer analysis of the various aspects involved shows that is uncharted territory both methodologically and in terms of content.